Association of Gestational Age With Postpartum Hemorrhage: An International Cohort Study. Issue 1 (23rd March 2022) - Butwick, A.J.; Liu, C.; Guo, N.; Bentley, J.; Main, E.K.; Mayo, J.A.; Shaw, G.M.; Stephansson, O.
Abstract : ( Anesthesiology . 2021:874–886. doi: 10.1097/ALN:0000000000003730) Although postpartum hemorrhage is a leading cause of preventable maternal death and morbidity in developed countries, 39% of women in the United States with severe postpartum hemorrhage do not have identified risk factors. All pregnant women are given risk assessment for common reasons of postpartum hemorrhage including preeclampsia, multiple gestations, labor induction, cesarean delivery, and chorioamnionitis. A factor not commonly used on risk assessments is gestational age at delivery. Data collected from previous in vitro studies showed inconsistent and conflicting associations between gestational age and postpartum hemorrhage. Some studies indicated there was a greater risk in women who delivered preterm, while others indicated postterm delivery posed the greatest risk. Differences in reporting methods between countries may also contribute to a lack of consistent data to show a strong relationship between gestational age and postpartum hemorrhage. The aim of this study was to assess and compare the association of gestational age and postpartum hemorrhage in the United States and Sweden.